Decadal Variations in Radiocarbon in Dissolved Inorganic Carbon (DIC) Along a Transect in the Western North Pacific Ocean. Issue 2 (27th January 2022) - Ge, Tiantian; Luo, Chunle; Ren, Peng; Zhang, Hongmei; Chen, Zhaohui; Sun, Shuwen; Xu, Liping; Wang, Xuchen
Abstract: We report results for the concentrations and radiocarbon ( 14 C) compositions of dissolved inorganic carbon (DIC) in water samples collected from a north‐south transect in the western North Pacific (NP) Ocean in November 2019 and compare our results with values previously reported for similar transects during the WOCE and CLIVAR projects decades ago. We show that the strong bomb 14 C penetration signal in the upper waters has gradually been reduced and diluted by deep water depleted in 14 C‐DIC over the last 30 years. The rate of decrease in Δ 14 C‐DIC values in surface waters was greater from 2005 to 2019 than from 1993 to 2005, and the rates of decrease from 2005 to 2019 were fastest (5.4–7.0‰ yr −1 ) between 25° and 32°N and slowest (2.1–2.8‰ yr −1 ) between 13°N and 16°N. The downwelling of the water mass could have accelerated the transport of bomb 14 C in the NP subtropical gyre (25°–32°N). The different decadal changes in Δ 14 C‐DIC in the North Pacific Intermediate Water (NPIW) from north to south prove that bomb 14 C is transported southward to the southwestern NP and that the bomb 14 C peak likely penetrates the ocean interior gradually. Changes in isopycnic circulation and advection diffusion in deep waters might have resulted in shifts in the baseline Δ 14 C‐DIC signature. Plain Language Summary: Dissolved inorganic carbon (DIC) in the ocean is the largest pool of exchangeable carbon in the world and plays dominant roles in the global carbon cycle. The North Pacific (NP) Ocean is an important, highly dynamic region that accounts for ∼25% of the annual CO2 global ocean sink from the atmosphere. To study the sources and cycling of DIC in the western NP, we measured radiocarbon, a powerful tracer, in DIC in water samples collected from 26 stations along a transect in the western NP in November 2019. We compared our results with data reported for similar transects in the NP sampled during the World Ocean Circulation Experiment (WOCE) and the Climate Variation and Predictability Program (CLIVAR) decades ago. The large data set enables us to evaluate the decadal changes in DIC concentrations and radiocarbon compositions in the western NP and to gain fresh knowledge about the carbon cycles linked to water circulation and mixing processes in the western NP. Key Points: Strong bomb 14 C signals are well mixed into the upper 200–500 m water depth through air‐sea exchange long a transect in the western NP Ocean Distribution of radiocarbon in DIC in the Kuroshio Extension region was influenced strongly by Oyashio Currents carrying low Δ 14 C values Bomb 14 C penetration signal in the NP has been reduced and diluted by deep waters carrying depleted 14 C‐DIC over the last 30 years